Livelihood Change and Household Strategies: Social Displacement of the Upper Class in Dhading - Luintel, Youba Raj (Dhaulagiri Journal of Sociology and Anthropology, 2015)
This article examines livelihoods transition among agrarian households in a cluster of villages adjacent to Kathmandu in a post-Neoliberal context. It specifically looks at the way these households respond to capitalist expansion in Nepal’s agrarian rural setting privileged to draw cash earnings. Looked at from the quest of longer term social change, this article identifies a great deal of similarity in household responses along class lines, and thus, concludes that household strategies broadly embrace class-specific behaviour. In identifying patterns of household response, this article also argues that class-differentiated analysis of household response can potentially illuminate social science understanding of the way capitalism penetrates into the countryside and brings social differentiation. Finally, this article demonstrates that social differentiation of agrarian households in rural Nepal is a mechanism of siphoning off of the rural surplus somewhere else (in this research context Kathmandu)–a mechanism widely attributed for an uneven development and underdevelopment of countryside Nepal.